Relationship between natural occurrence of banana streak badnavirus and symptom expression, relative concentration of viral antigen, and yield characteristics of some micropropagated Musa spp - Dahal, G.; Ortíz, R.; Tenkouano, A.; Hughes, J.; Thottappilly, G.; Vuylsteke, D.R.; Lockhart, B.E.L. (Wiley, 2000)
Micropropagated plants of 36 Musa genotypes with diverse genetic backgrounds, including 14 tetraploid plantain (TMPx) and banana (TMBx) hybrids, were evaluated for their response to banana streak badnavirus (BSV) infection under three environments from 1995 to 1997 in Nigeria. The characteristics evaluated were the natural incidence of BSV based on symptoms and virus indexing, relative concentration of BSV antigens in leaf tissues determined by ELISA, and some growth and yield descriptors. Virus occurrence and symptom expression, as well as the relative concentration of BSV antigens, fluctuated greatly between seasons during the cropping cycle, being high during the rainy season and low or negligible during the hot dry season. The natural incidence of plants with symptoms and BSV-infected plants varied between genotypes. Incidence of BSV on most International Institute of Tropical Agriculture (IITA) TMPx hybrids and three Fundación Hondureòa de Investigación Agrìcola (FHIA) hybrids was high in the three environments, with some variation. Most landraces and some FHIA or Empresa Brasileira de Pesquisa Agropecuaria (EMBRAPA) hybrids were not BSV-infected under either environment at Onne. However, a few expressed some foliar symptoms at Ibadan and indexed BSV positive. The relative concentration of BSV antigens in leaf samples was also high in most TMPx and some FHIA hybrids, but low in most landraces. While BSV infection had no significant effect on most growth characteristics, it had a highly variable effect on bunch weight loss among the genotypes. There was no relationship between the natural incidence of BSV, concentration of viral antigen and bunch weight loss among the 11 TMPx hybrids, three FHIA hybrids and three plantain landraces. Despite the high natural BSV incidence and the high relative antigen concentration in their leaf tissue, TMPx 548-9, TMPx 2637-49, TMPx 7002-1 and FHIA 21 suffered less than 15% bunch weight loss, and TMPx 548-4 and FHIA 22 suffered no loss. These results suggest that under the conditions specified in this study, these hybrids could be tentatively classified as ‘field tolerant’ to BSV.